Human development - Papalia, Diane E; Olds, Sally Wendkos (McGraw-Hill, 1992)
This updated text emphasizes the continuity of human development throughout the lifespan with an increased emphasis on cross-cultural issues. A case study on language development introduced in the first chapter, serves as a springboard for the discussion of developmental issues.
Keywords: vývojová biologie; biologie; psychologické jevy a procesy; psychologie, klinická psychologie; fyziologie; sociologie; Developmental Biology; Psychological Phenomena